The effect of metacognitive and cognitive Strategies upon EFL learner’s reading comprehending developments with emphasizing to student’s linguality knowledge - Abbasi, Peyman (Technium Business and Management, 2022)
Reading comprehension ability is the potency of students that they can grasp the meaning of the written texts and the reading text details and the main ideas. Furthermore, the ability of reading comprehension activated the learners to communicate with the writers. To understand the main ideas of the written texts helps the learner to be aware and to get particular messages from the texts. The metacognitive and cognitive knowledges can help the readers to analyze, to summarize, to judge, and to distinguish the main idea of the reading texts and also the more details about the writer viewpoints to predicate and decision making to monitor the text contents too.